The Role of Ancient Egyptian Civilization in the Islamic Astronomical Revolution of the Abbasid Era - Alpaten, Ulil Albab Al aulia; Mahsun; Izzuddin, Ahmad (Universitas Islam Negeri Mataram, 2024)
This study investigates the important role of Ancient Egyptian civilization in the development of science during the Abbasid era. Through a literature review, this study outlines the history of Ancient Egypt and its contribution to falak, explains the Abbasid era as a historical context, and analyzes the development of falak during the Abbasid period. Research methodology includes methods of resource analysis, collection of data from various sources, and application of relevant analytical techniques. The results showed that Ancient Egyptian civilization had a major role in the development of Abbasid Era science. This is seen in the transfer of knowledge, astronomical advances, translations of classical works, improvements to the Hijri calendar, and the impact on navigation. Innovation, recognition of cultural and knowledge diversity, and advances in science are driven by integration. The results suggest that the integration of culture and knowledge can enable the development of scientific knowledge. In the current context of global openness of science, this has relevance. This study enhances science and increases our understanding of how different civilizations affect science. This study concludes that Ancient Egyptian civilization had an important role in the progress of science in the Abbasid era, thus encouraging progress, foundation formation, and influence of science to this day.